Basic Training on Air Conditioner (AC) Maintenance and Repair for Musala Janitors in Padang City - Herizon, Herizon; Yuliza, Milda; Wirda, Fisla (Research and Social Study Institute, 2023)
The high temperature in Padang City, between 22.90 and 34.80oC, causes air conditioner (AC) to become a necessary equipment to provide cool and comfortable air in every room. The use of AC will have an impact on the need for experts in the field of AC maintenance and repair. This training aimed to provide knowledge and skills to participants regarding AC maintenance and repair, as well as optimizing the use of energy to save operational costs. The methods used in this training were the introduction of theory, demonstration, and practice by a trainer team experienced in the field of AC technology. The training materials provided were the introduction, basic understanding of AC technology, maintenance and repair methods, and energy saving. The training began with a delivery of the practice-supporting theory, in the form of material on AC basic components and working systems. This material was delivered through lecture, discussion, and question and answer session. This was followed by a practice using the AC trainer module. Participants were given an understanding on how to clean the AC (both indoor and outdoor systems), check the working system, observe the malfunction symptoms, and the causes of AC malfunction. This training was attended by two participants, namely the janitors of Musala Arafah in Puri Filano Asri Kubu Dalam, Padang City. The success level of this training was evaluated through oral test, interview, and practice test. The results showed that this training was able to increase the participants' knowledge about observing symptoms and causes of AC malfunction and equip participants with the necessary skills to perform basic AC maintenance and repair.